The Role Of Youth Force Muhammadiyah (Amm) In Developing The Suprastructure And Youth Infrastructure In KNPI South Sulawesi - Soemitro Emin Praja; Abdul Razak Munir; Lukman Irwan (Department of Public Administration, Muhammadiyah University of Makassar, 2021)
This study aims to see how the role of AMM is in improving the youth superstructure as well as the role of AMM in improving youth infrastructure in KNPI, South Sulawesi. This research uses descriptive qualitative research. The number of informants in this study was the technique of studying the data in this study, observation, interviews, and documentation. The results showed that the role of the Muhammadiyah youth (AMM) in the superstructure of development and youth infrastructure in the South Sulawesi KNPI responded to the reality of advocating and promoting action as a forum for struggle, then reviving communication forums through discussion activities such as social dialogue, then youth and nationality and local-based FGDs on an ongoing basis, as well as becoming a cadre laboratory as a process of youth regeneration efforts in South Sulawesi, and increasing harmonization, solidity and synergy as an effort to cement the OKP plurality in KNPI South Sulawesi. Suggestions in this study are the Chairman of KNPI Sulsel to further promote youth values in terms of infrastructure and youth superstructure. Penelitian ini bertujuan untuk mengetahui bagaimana peran AMM dalam pembenahan suprastruktur kepemudaan serta bagaimana peran AMM dalam pembenahan infrastruktur kepemudaan di KNPI Sulawesi Selatan. Penelitian ini menggunakan jenis penelitian deskripsi Kualitatif. Adapun jumlah informan dalam penelitian ini berjumlah 6 orang. Teknik pengumpulan data dalam penelitian ini, yaitu observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa peran angkatan muda muhammadiyah (AMM) dalam pembangunan suprastruktur dan infrastruktur kepemudaan di KNPI Sulawesi Selatan merespon realitas yakni melakukan advokasi dan menggalakkan aksi sebagai wadah perjuangan, kemudian menghidupkan forum-forum komunikasi melalui kegiatan diskusi seperti dialog social kemasyarakatan, kemudian kepemudaan dan kebangsaan serta FGD yang berbasis local secara berkesinambungan, serta menjadi laboratorium kader sebagai proses upaya regenerasi kepemudaan di Sulawesi selatan, dan meningkatkan harmonisasi, soliditas dan sinergitas sebagai upaya merekatkan kemajemukan OKP yang ada di KNPI Sulawesi Selatan. Saran dalam penelitian ini adalah Ketua umum KNPI Sulsel agar lebih menggalakkan lagi nilai-nilai kepemudaan dari segi infrastruktur dan suprastruktur kepemudaaan.